Induced resistance to periwinkle grazing in the brown seaweed Fucus vesiculosus (Phaeophyceae): molecular insights and seaweed‐mediated effects on herbivore interactions. Issue 3 (3rd May 2014) - Flöthe, Carla R.; Molis, Markus; John, Uwe; Amsler, C.
<x xml:space="preserve">Abstract</x> Herbivory is a key factor for controlling seaweed biomass and community structure. To cope with grazers, constitutive and inducible defenses have evolved in macroalgae. Inducible chemical defenses show grazer‐specificity and, at the same time, have the potential to mediate interactions among different herbivores. Furthermore, temporal variations in defense patterns, which may adjust antiherbivory responses to grazing pressure, were reported in two brown seaweeds. However, underlying cellular processes are only rudimentarily characterized. To investigate the response of Fucus vesiculosus (L.) to periwinkle (Littorina obtusata) grazing, feeding assays were conducted at several times during a 33 d induction experiment. Underlying cellular processes were analyzed through gene expression profiling. Furthermore, direct processes driving the antiherbivory response to periwinkle grazing and indirect effects on another herbivore, the isopod Idotea baltica, were elucidated. F. vesiculosus showed multiple defense pulses in response to periwinkle grazing, suggesting a high level of temporal variability in antiherbivory traits. Defense induction was accompanied by extensive transcriptome changes. Approximately 400 genes were significantly up‐/down‐regulated relative to controls, including genes relevant for translation and the cytoskeleton. Genes involved in photosynthesis were mostly down‐regulated, while genes related to the respiratory chain were up‐regulated, indicating alterations in resource allocation. The comparison of genes regulated in response to isopod (previous study) and periwinkle grazing suggests specific induction of several genes by each herbivore. However, grazing by both herbivores induced similar metabolic processes in F. vesiculosus. These common defense‐related processes reflected in strong indirect effects as isopods were also repelled after previous grazing by L. obtusata.